A Review on Preparation of Medium Density Fiberboard with Different Materials - Pugazhenthi, N; Anand, P (International Journal of Engineering and Technology, 2018)
The number of papers had reviewed on natural composites recently, but related to medium density fiberboard there is no any review. So this paper completely concentrates on the preparation of medium density fiberboard. The MDF plays an important role in wood industries for manufacturing the furnitureâ€™s and interior design at home. Generally MDF was prepared with fibers and with some synthetic resins, additives if necessary. There were various fibers and resins used to prepare the board for different applications. Here this paper describes about the various types of materials like wheat straw, banana stem, rubber wood, etc., and various resins like urea formaldehyde, phenol formaldehyde, etc., were used for the preparation of MDF. The main purpose of discussing about MDF preparation was to know different methods of making the board. This will helps the researchers for further research on MDF material selection and processing of board making.Â Â